Profiling of Virulence Factors and Antibiotic Resistance Genes Among Phylogenetic Groups of Extended-Spectrum-Beta-Lactamase Producing Escherichia Coli - Yahya Abdullah Al-Hetar, Khadega (2011)
Extra-intestinal infection caused by Escherichia coli arose in recent years throughout the world. Dissemination of antibiotic resistant strains especially resistant to beta-lactams make the E. coli infections difficult to be treated. Presence of commensal E. coli that are resistant to beta-lactams among extraintestinal infections plays an important role in disseminating antibiotic resistance among different microorganisms. Phylogenetically E. coli are classified into four main phylogenetic groups A, B1, B2 and D by the presence of chuA, yjaA and TsPE4C2 genes. The virulent extra-intestinal strains mainly belong to group B2, and to a lesser extent to group D and harbor many types of virulence genes, whereas most commensal strains belong to group A and B1 with low virulence genes. The ESBLs are known to be produced more in low virulent strains than in high virulent strains. It is important to determine the factors that make commensal E. coli resistant to drug and also cause infections. Therefore the goal of the current study is to investigate the association between antibiotic resistance and virulence factors among different phylogenetic groups which play a vital role in the management of infections. In the current study 95 clinical isolates of Extended spectrum beta-lactamase (ESBL)-E. coli collected from various infections from Selayang Hospital in Malaysia were investigated. The isolates were phylogenetically classified, followed by ESBL typing and important virulent determinants such as adhesions and toxins determination. Among the 95 isolates 42 (44%), 26 (27%), 14 (14.7%) and 13 (13.7%) belonged to groups D, A, B2 and B1. Based on the antibiotic susceptibility test most isolates showed resistance to antibiotics as following; cefotaxime (n=78; 82.11%), ampicillin/sulbactam (78; 82.11%), sulfamethaxazole/trimethoprim (77; 81.1%), azetronem (70; 73.7%), cefepime (53; 55.79%), and ampicillin (n=95; 100%). Investigation on the genes coding for the beta-lactamase enzymes among the E. coli isolates showed that majority (58.9%) belonged to the CTX-M-1-type with CTX-M-15 as the predominant sub type. CTX-M-9 cluster was significantly higher among pathogenic group than commensal group (P<0.05), while CTX-M-1 cluster was found more among commensal (61.5%) than pathogenic (57.7%) group. However, no significant association between the groups was observed (P>0.05). TEM was detected in 8 (8.4%) isolates while SHV was rare; twelve (12.6%) isolates did not carry any resistance genes. Among the six virulence genes (iutA, hlyA, sfa/foc, afa/dra, kpsMII and pap) investigated in the ESBL-E. coli isolates, iutA was found to be more prevalent (n=56, 59%) followed by kpsMII (n=33, 34.7%). Genes coding for afa/foc was not detected in any isolate while sfa/foc and hlyA were rarely seen. Among the total isolates (n=95) tested 27 (28%) did not carry any of virulence factors. Analyzing the association between pathogenic and commensal groups for iutA did not show any significant association for pathogenic and commensal (P>0.05) while the kpsMII was highly significant (P<0.05) for pathogenic group. In conclusion isolates of CTX-M types producing virulent E. coli strains among commensal groups isolated from extra-intestinal infections warrants the urgent need for the control of such pathogen as it not only increases the infection rate but also has the potential to spread antibiotic resistance and virulence to other nosocomial pathogens.